Investigacion en fincas: validacion o prueba de tecnologia ICTA en la region sur-oriental: Validacion de variedades, el rol del mejorador, extensionista y agricultor - Heer, CE (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
The process of technology transfer and evaluation, carried out in Guatemala by the Instituto de Ciencia y Tecnologia Agricolas, is described. This process involves agro-socioeconomic studies, identification of production constraints, technology generation in research centers, and on-farm validation of generated technology with the participation of farmers and extension workers. Problems mainly occured between researchers and extension workers, but were solved by enhancing the participation of extension workers throughout the whole process. Comments are made on trial plot size, knowledge of the area, and selection of participating farmers. Technology transfer in other countries is mentioned. (CIAT)